Antecedents of ICT managers’ ethical leadership and its influence on employee turnover intention - Kumarusamy, Risidaxshinni (2019)
The Information and Communications Technology (ICT) industry faces serious turnover and leadership issues, especially among the younger generation of employees. While ethical leadership is proven to reduce turnover intention and attract younger employees, little is known about the antecedents to ethical leadership and how this leadership style influences employees’ intention to leave. Therefore, this study attempted to establish multilevel antecedents to ICT managers’ ethical leadership, which were emotional intelligence and collectivism at the individual level, and ethical climate and person-organisation fit at the contextual level. This study also investigated employee engagement as a mediator between ethical leadership and ICT employees’ turnover intention. Data was collected from a matched sample of 212 managers and 387 of their direct subordinates from Malaysian MSC-status ICT companies, and was analysed using PLS-SEM. The results of the analysis proved that emotional intelligence, collectivism, and person-organisation fit are significant predictors of ethical leadership. Ethical climate was also found to impact ethical leadership, such that benevolent and principled climates significantly improve ethical leadership while egoism climate lowers it. For the ICT industry in particular, this study revealed that ethical leadership is a significant factor that reduces the turnover intention of employees. This study, in addition, established employee engagement as a significant mediating mechanism through which ethical leadership reduces employees’ intention to leave. In short, the current study has expanded the ethical leadership antecedent literature and offers practitioners valuable tools in the selection and development of ethical leaders. It also deepens the understanding of the ways ethical leadership exerts influence on followers, as well as proves ethical leadership’s efficacy in reducing the high turnover that is plaguing the ICT industry. Future studies should explore additional antecedents of ethical leadership as well as its effects on employees in different industries. Finally, the current study confirmed that managers rate themselves higher on ethical leadership measures than employees’, making employees’ ratings more reliable for empirical research. Thus, multiple sources, as those used in this study (managers and direct subordinates), should be used to reduce single source bias and common method variance in future ethical leadership studies.